2022
DOI: 10.3389/fonc.2022.918693
|View full text |Cite
|
Sign up to set email alerts
|

Oncological Safety of Diagnostic Hysteroscopy for Apparent Early-Stage Type II Endometrial Cancer: A Multicenter Retrospective Cohort Study

Abstract: ObjectiveTo study the oncological safety of diagnostic hysteroscopy for women with apparent early-stage type II endometrial cancer.Patients and MethodsA total of 429 women with presumed early-stage type II endometrial cancer were included. The 5-year disease-free survival (DFS) and overall survival (OS) were estimated and compared using the Kaplan-Meier method and the log-rank test among patients diagnosed by Dilation & Curettage (D&C) or diagnostic hysteroscopy. The Cox proportional hazards re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“… 1 , 2 Hysteroscopy is one of the most common minimally invasive procedures for the diagnosis and treatment of uterine diseases. 3 , 4 In order to relieve the anxiety and tension of patients and successfully complete hysteroscopy, propofol is widely used for hysteroscopic sedation. 5 , 6 Propofol exerts its sedative effect mainly by activating gamma amino butyric acid (GABA) receptors.…”
Section: Introductionmentioning
confidence: 99%
“… 1 , 2 Hysteroscopy is one of the most common minimally invasive procedures for the diagnosis and treatment of uterine diseases. 3 , 4 In order to relieve the anxiety and tension of patients and successfully complete hysteroscopy, propofol is widely used for hysteroscopic sedation. 5 , 6 Propofol exerts its sedative effect mainly by activating gamma amino butyric acid (GABA) receptors.…”
Section: Introductionmentioning
confidence: 99%
“…There were no differences between the 5‐year DFS rates and 5‐year OS rates of the diagnostic hysteroscopy group and that of the D&C group. 22 Moreover, a recent study published by Quintana‐Bertó R et al compared relapse and survival rates in 1731 women who had been evaluated by either pipelle biopsy or hysteroscopy in a retrospective multicentric study and found no impact on oncological outcomes. 23 The present study reports agree with these findings.…”
Section: Discussionmentioning
confidence: 99%
“…They found that 80% of cytology conversions occurred at the third washing, implying that the presence of the manipulator in the uterine cavity during the whole procedure is the main issue, rather than the insertion of the manipulator itself 16 . Interestingly, hysteroscopy has been associated with higher PPC rates, but without worse oncological outcome [26][27][28][29] . This discrepancy might result from different ways of handling the IU device.…”
Section: Discussionmentioning
confidence: 99%